Pengaruh Podcast Edukatif dan Brand Awareness terhadap Customer Engagement Mahasiswa Telkom University - Akhiva Jeven Christian; Rahmat Hidayat; Laksmi Saraswati Hadiansyah (Jesya, 2026)
This study examines the extent to which Educational Podcasts and Brand Awareness influence student engagement on the Ready Radio Channel of the Communication Studies Department at Telkom University not merely by measuring “likability,” but by establishing a causal relationship between listening experiences, brand recall, and engagement as reflected in audience behavior. A quantitative approach was chosen as a lens that forces empirical arguments to meet numbers: data was collected online via a Google Form questionnaire, so that response traces became a timeline that could be replicated and retested. The population consists of active students who have interacted with the channel people who are bombarded with content daily, yet here are systematically asked: who is truly “present” and listening, rather than merely scrolling through the news feed? The final sample comprises 92 respondents, selected through sampling logic not as a decorative number, but as a balance between limited representativeness and analytical feasibility. Behind the scenes in SPSS version 21, a series of tests runs like a chain of data quality checks: Pearson Product-Moment validity to ensure that the instrument’s items measure the same variable; Cronbach’s Alpha reliability to see if responses are consistent across measurement rounds; followed by classical assumption tests for normality, multicollinearity, heteroscedasticity, and autocorrelation, which function as statistical filters before multiple linear regression is permitted to proceed. At the inference stage, the t-test and F-test pose two distinct questions regarding the same model: what is the partial effect of each predictor, and does the simultaneous combination of predictors truly explain the variation in Customer Engagement? The findings confirm a consistent yet nuanced narrative: Educational Podcasts have a positive and significant effect on student Customer Engagement evidence that audio designed to teach, prompt reflection, or spark discussion is more than just entertainment in between campus activities. Brand awareness is equally important as a driver of engagement; moreover, together these two variables have a simultaneous, positive, and significant effect, with brand awareness playing a more dominant role in explaining variations in engagement than educational podcasts. This means that within the campus channel ecosystem, a recognizable name and the meaning associated with that channel can act as a “cognitive magnet” that makes it easier for listeners to move into the next behavioral layers commenting, sharing, repeated consumption, and listening loyalty before the content itself has a chance to take the lead. Theoretically, these results align campus empirical experiences with the logic of customer engagement: when the quality of educational podcast content meets mature brand awareness, engagement ceases to be a vague phenomenon and begins to be understood as a combination of content competence and the audience’s mental capital toward the channel’s brand. For higher education communication practitioners, the implication is almost like the analogy that good podcast infrastructure is a smooth path, but brand awareness is the map that makes people choose that path again and again.